Pengaruh Agresivitas Pajak Pada Corporate Social Responsibility dengan Profitabilitas sebagai Variabel Moderasi - Jananti, Ni Wayan Ristiari; Setiawan, Ery (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
A company has a social and environmental responsibility to make a profit. Corporate social responsibility (CSR) is the company's commitment to be responsible for the impact of the company's operations on social, economic and environmental dimensions. The high level of CSR disclosure of a company can be affected by tax aggressiveness and profitability. This study aims to determine the effect of tax aggressiveness on CSR and to determine whether profitability moderate the influence of tax aggressiveness on CSR.This study focuses on property and real estate sector in Indonesia Stock Exchange. The method of determining the sample used is non probability sampling with purposive sampling technique. Data collection using non participant observation method. “ Data analysis technique used is test of Moderated Regression Analysis (MRA). ” The results showed that tax aggressiveness has a positive effect on CSR and profitability able to moderate the influence of tax aggressiveness on CSR. The implications of the research, theoretically proving the theory of legitimacy in the context of tax aggressiveness and are practically expected to contribute positively to the parties concerned. Keywords : corporate social responsibility, tax aggressiveness, profitability .